Analysis of the antenatal fetal death frequency in pregnant women in Odessa region for the years 2007–2011 - L. R. Nikogosyan (Zaporožskij Medicinskij Žurnal)
In Odessa region from 2007 to 2011 specifi c gravity of antenatal death of feti constituted 1,01% from the general amount of births, and their frequency was 10,1‰. Specific gravity of аntenatal losses of feti diminished from 1,9% in 2007 to 0,6% in 2011, and frequency - from 19,1‰ in 2007 to 5,8‰ in 2011. In Odessa-city antenatal death of fetus was 1,1% from the general amount of births, or 10,8 on 1000 births. Specific gravity of prematurely born at antenatal death of fetus in Odessa region makes 77,5%. Antenatal death of fetus with mass up to 1000 g made 68,6% from the general amount of prematurely born. In Odessa the corresponding data constitute 81,0% and 77,8%.